Sn-Cu3Sn1 / Cu catalyst, preparation of Sn-Cu3Sn1 / Cu catalyst, supported copper-tin catalyst electrode and preparation and application of supported copper-tin catalyst electrode

By using Sn-Cu3Sn1/Cu catalyst, the problems of low Faraday efficiency and by-product C4 in electrocatalytic acetylene hydrogenation reaction are solved, and the effects of high ethylene selectivity and high Faraday efficiency are achieved.

CN119800423AActive Publication Date: 2025-04-11ZHEJIANG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411970077.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the existing electrocatalytic acetylene hydrogenation reaction, the copper-based catalyst has problems with low Faraday efficiency and the generation of by-product C4, which affects the selectivity of ethylene.

Method used

Sn-Cu3Sn1/Cu catalyst is used to form a Cu3Sn1 alloy layer on the surface of copper nanoparticles, and Sn atoms are grown as termination positions at the Sn site. The conversion rate and selectivity of the catalyst are improved through specific preparation methods and electrode preparation techniques.

Benefits of technology

It achieves high catalytic activity, effectively inhibits the production of hydrogen and C4, improves the selectivity of ethylene and Faraday efficiency, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005219307910000011
    Figure HDA0005219307910000011
  • Figure HDA0005219307910000021
    Figure HDA0005219307910000021
  • Figure HDA0005219307910000031
    Figure HDA0005219307910000031
Patent Text Reader

Abstract

The invention discloses a Sn-Cu3Sn1 / Cu catalyst and preparation thereof, and a copper-tin-loaded catalyst electrode and preparation and application thereof. According to the microstructure of the Sn-Cu3Sn1 / Cu catalyst, a Cu3Sn1 alloy layer is formed on the surfaces of copper nanoparticles through reconstruction, and Sn atoms are grown on Sn sites of Cu3Sn1 alloy to serve as stop sites. The supported copper-tin catalyst electrode is obtained by uniformly mixing slurry containing the Sn-Cu3Sn1 / Cu catalyst and a nafion solution with the mass fraction of 5%-25%, uniformly coating an electrode material with the mixed slurry and then drying. The invention provides the application of the supported copper-tin catalyst electrode in electro-catalysis acetylene selective hydrogenation reaction, and the supported copper-tin catalyst electrode has the advantages of high conversion rate, high selectivity and high Faraday efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic acetylene selective hydrogenation, and specifically relates to a Sn-Cu3Sn1 / Cu catalyst and a preparation method thereof, a copper-tin loaded catalyst electrode and a preparation method thereof, and an application thereof in an electrocatalytic acetylene selective hydrogenation reaction. Background Art

[0002] Ethylene is an important component in chemical synthesis. However, the crude ethylene gas produced industrially contains 0.1-2.0% acetylene by volume. The strong coordination of acetylene can cause poisoning and deactivation of the (Ziegler-Natta) catalyst for ethylene polymerization. Therefore, it is necessary to remove acetylene from the ethylene raw material.

[0003] The conditions for the thermal catalytic acetylene hydrogenation reaction usually require a temperature of more than 200°C, a pressure of about 5 atmospheres, and the hydrogenation source is expensive hydrogen. In addition, the thermal catalytic acetylene selective hydrogenation reaction often uses precious metal palladium as a catalyst, which has the problem that acetylene is easily over-hydrogenated to ethane and the selectivity of ethylene is low.

[0004] Compared with the traditional thermal catalytic acetylene hydrogenation process, the electrocatalytic acetylene selective hydrogenation reaction has the advantages of high selectivity, mild reaction conditions and low cost, and the added hydrogen atoms come from the dissociation of water molecules in the electrolyte solution, eliminating the cost and safety hazards of hydrogen production, transportation and storage. Copper-based catalysts are commonly used in electrocatalytic acetylene hydrogenation reactions, which have the advantages of high catalytic performance and low price. This shows that this technology has great potential. However, copper-based catalysts also show good catalytic effects in hydrogen evolution. And the acetylene intermediates activated on the surface of copper-based catalysts may undergo CC coupling reactions to produce butadiene, isobutylene and other (C4) by-products. The existence of side reactions leads to the problem of low Faraday efficiency of copper-based catalysts.

[0005] Based on the above prior art, the inventors hope to invent a catalyst that exhibits high catalytic activity in the electrocatalytic acetylene hydrogenation reaction and can effectively inhibit the production of hydrogen and C4, thereby improving ethylene selectivity and Faraday efficiency. Summary of the invention

[0006] In order to improve the electrocatalytic selective hydrogenation of acetylene to produce ethylene and effectively inhibit the production of hydrogen and C4, the present invention provides a Sn-Cu3Sn1 / Cu catalyst with high conversion rate, high selectivity and high Faraday efficiency and a preparation method thereof, a loaded copper-tin catalyst electrode and a preparation method thereof and an application in the electrocatalytic acetylene hydrogenation reaction.

[0007] The present invention specifically adopts the following technical solutions:

[0008] In the first aspect, the present invention provides a Sn-Cu3Sn1 / Cu catalyst, whose microstructure is a Cu3Sn1 alloy layer (copper atoms and tin atoms are regularly arranged) reconstructed on the surface of copper nanoparticles, and Sn atoms are grown on the Sn sites of the Cu3Sn1 alloy as termination sites.

[0009] In a second aspect, the present invention provides a method for preparing the Sn-Cu3Sn1 / Cu catalyst described in the first aspect, which is carried out according to the following steps:

[0010] Step 1: dissolving copper salt and tin salt in water and stirring to prepare solution A, wherein the molar ratio of Sn / Cu is 0.01-0.2, preferably 0.04-0.06;

[0011] Step 2: Prepare a solution with a concentration of 0.1-10 mol L -1 of sodium borohydride aqueous solution B;

[0012] Step 3: Rapidly add sodium borohydride aqueous solution B into solution A at -10°C to 25°C and let stand for 2-6 hours;

[0013] Step 4: Collect the solid in the solution, wash, and dry to obtain the Sn-Cu3Sn1 / Cu catalyst.

[0014] Preferably, the copper salt described in step 1 is selected from at least one of copper chloride, copper nitrate, copper sulfate, copper phosphate, copper pyrophosphate, basic copper carbonate and copper acetate.

[0015] Preferably, the tin salt in step 1 is selected from at least one of stannous chloride, tin tetrachloride, tin nitrate and stannous sulfate.

[0016] In step 3 of the present invention, the feeding ratio of the sodium borohydride aqueous solution B and solution A is preferably such that the sodium borohydride in solution B can completely reduce the metal ions in solution A to zero-valent metals, and preferably the sodium borohydride is in excess.

[0017] Preferably, in step three, the temperature is controlled at -10°C to 5°C, more preferably at 0°C.

[0018] Preferably, the drying in step 4 is carried out in a vacuum oven at 40°C-120°C for 6-12 hours.

[0019] Preferably, in step 4, the washing reagents are water and ethanol.

[0020] In a third aspect, the present invention provides a copper-tin catalyst loaded electrode, which is obtained by uniformly mixing a slurry containing the Sn-Cu3Sn1 / Cu catalyst described in the first aspect and a nafion solution with a mass fraction of 5%-25%, uniformly coating the mixed slurry on an electrode material, and then drying it.

[0021] Preferably, the concentration of the slurry containing the Sn-Cu3Sn1 / Cu catalyst is 0.5-10 mg ml -1 The ratio of the volume of the slurry containing the Sn-Cu3Sn1 / Cu catalyst to the volume of the nafion solution is 2500:30-200. It is further preferred that the concentration of the slurry containing the Sn-Cu3Sn1 / Cu catalyst is 10 mg ml -1 The mass fraction of the nafion solution is 5%, and the ratio of the volume of the slurry containing the Sn-Cu3Sn1 / Cu catalyst to the volume of the nafion solution is 2500:150.

[0022] Preferably, the electrode material is at least one of carbon paper, carbon cloth, nickel foam and copper foam.

[0023] As a further preference, the electrode material is carbon paper, and the loading amount of the mixed slurry on the carbon paper is 0.1-2 mg / cm 2 , and more preferably 0.8 to 1.2 mg / cm 2 .

[0024] In a fourth aspect, the present invention provides a method for preparing the copper-tin catalyst electrode supported by the third aspect, which is carried out according to the following steps:

[0025] Step A: Take Sn-Cu3Sn1 / Cu catalyst and add it to the solvent to make 0.5-10mg ml -1 The ink-like slurry is then added with a 5%-25% by mass nafion solution, and the mixed slurry is subjected to ultrasonic treatment to be fully dispersed;

[0026] Step B: washing the cut electrode material (preferably with hydrochloric acid, ethanol and deionized water) and then drying;

[0027] Step C: evenly apply the mixed slurry obtained in step A to the electrode material obtained in step B, and irradiate with an infrared lamp until the slurry is completely dry to obtain a copper-tin catalyst-loaded electrode.

[0028] Preferably, the solvent in step A is selected from at least one of deionized water, acetone, ethanol, isobutanol, ethylene glycol, n-propanol and isopropanol.

[0029] Preferably, the ultrasonic wave used in step A has a frequency of 20-100 kHz and an ultrasonic time of 0.5-3 hours.

[0030] Preferably, in step A, the ratio of the volume of the slurry containing the Sn-Cu3Sn1 / Cu catalyst to the volume of the nafion solution is 2500:30-200. More preferably, the concentration of the slurry containing the Sn-Cu3Sn1 / Cu catalyst is 10 mg ml -1 The mass fraction of the nafion solution is 5%, and the ratio of the volume of the slurry containing the Sn-Cu3Sn1 / Cu catalyst to the volume of the nafion solution is 2500:150.

[0031] Preferably, the electrode material in step B is at least one of carbon paper, carbon cloth, nickel foam and copper foam.

[0032] As a further preference, the electrode material is carbon paper, and the loading amount of the mixed slurry on the carbon paper is 0.1-2 mg / cm 2 , and more preferably 0.8 to 1.2 mg / cm 2 .

[0033] Preferably, the infrared lamp power in step C is 100-300W, and the irradiation time is 10-60min.

[0034] In a fifth aspect, the present invention provides a use of the copper-tin supported catalyst electrode described in the third aspect in an electrocatalytic selective hydrogenation reaction of acetylene.

[0035] Preferably, the application is performed according to the following steps:

[0036] Step 1: Place the copper-tin catalyst electrode loaded on the cathode of the electrochemical device as the working electrode, select nickel foam or copper foam as the counter electrode, and use an ion exchange membrane and 0.5-2 mol L -1 The KOH electrolyte solution separates the two electrodes;

[0037] Step 2: introducing the raw material gas containing acetylene into the acetylene gas chamber of the electrocatalytic acetylene hydrogenation reaction system through the gas inlet;

[0038] Step 3: Turn on the power supply to make the working electrode at the reaction potential, and the acetylene gas diffuses to the working electrode to perform the electrocatalytic acetylene hydrogenation reaction, so that the acetylene is selectively hydrogenated into ethylene;

[0039] Step 4: Discharge the acetylene hydrogenation gas product from the acetylene gas chamber outlet.

[0040] Preferably, the electrochemical device in step 1 can be an H-type electrolytic cell or a flow electrolytic cell.

[0041] Preferably, the ion exchange membrane in step 1 is at least one of commercial ion exchange membranes such as a proton exchange membrane or an anion exchange membrane.

[0042] Preferably, the acetylene-containing raw gas in step 2 can be ethylene-rich gas with an acetylene concentration between 0.5% and 10%, or can be pure acetylene gas.

[0043] Preferably, the flow rate of the acetylene-containing feed gas in step 2 is 1 ml min -1 -60ml min -1 .

[0044] Preferably, the power source in step 3 is at least one of an electrochemical workstation, a constant current, and a constant voltage power source.

[0045] Preferably, in step 3, the reaction potential is 0 V to -1.5 V relative to the reversible hydrogen electrode.

[0046] Compared with the prior art, the present invention has the following innovations and advantages:

[0047] (1) The Sn-Cu3Sn1 / Cu catalyst described in the present invention uses the Sn termination site as the active center. Compared with the surface of Cu nanoparticles that are prone to carbon-carbon coupling reaction and hydrogen evolution reaction, the Sn termination site effectively avoids the formation of C4 byproducts and hydrogen.

[0048] (2) The use of Sn-Cu3Sn1 / Cu catalyst can convert acetylene into ethylene under the conditions of enlarged reactor and high flow rate of raw gas, which can create conditions for the large-scale application of electrocatalytic acetylene hydrogenation reaction.

[0049] (3) Compared with traditional thermal catalytic technology, the electrocatalytic acetylene selective hydrogenation reaction method of the present invention can reduce acetylene gas to ethylene at room temperature and pressure without consuming hydrogen, which can significantly improve the selectivity of the reaction and greatly reduce the energy consumption of the process, which is more in line with the requirements of green chemical industry and has great strategic significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 At -0.4V (Vvs.RHE) and 50ml min -1 The data diagram of the conversion rate of EASR reactants and the FE (%) of products using different catalysts at flow rates;

[0051] Figure 2 are XRD patterns of Cu, Sn-Cu3Sn1 / Cu, Sn / Cu, Cu6Sn4 and Cu6Sn5 catalysts prepared in Examples and Comparative Examples;

[0052] Figure 3 is the HAADF-STEM image of the Sn-Cu3Sn1 / Cu catalyst prepared in Example 1;

[0053] Figure 4 This is a schematic diagram of the one-step synthesis of Sn-Cu3Sn1 / Cu catalyst and EASR. DETAILED DESCRIPTION

[0054] The present invention is described below with specific examples. It is necessary to point out that the examples are only used to further illustrate the present invention, but cannot be understood as limiting the scope of protection of the present invention, and the present invention is not limited thereto in any way. A person skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0055] Example 1: Synthesis of Sn-Cu3Sn1 / Cu catalyst and its application in electrocatalytic acetylene hydrogenation reaction

[0056] Prepare solution A by dissolving 862 mg of anhydrous cupric chloride and 64 mg of stannous chloride in 10 ml of deionized water. Prepare 10 ml of 5 mol L -1 10 ml of sodium borohydride aqueous solution B was quickly added to 10 ml of A solution at 0 ° C and allowed to stand for 2 hours. The black solid in the solution was collected and then washed with water and ethanol several times. Dry in a vacuum oven at 40 ° C for 12 hours. The obtained catalyst was named Sn-Cu3Sn1 / Cu. The XRD pattern and HAADF-STEM image of the Sn-Cu3Sn1 / Cu catalyst are shown in Figure 2 and Figure 3 ; Figure 2 The XRD spectrum shows that the Sn-Cu3Sn1 / Cu catalyst is mainly composed of Cu phase, a small amount of Cu3Sn1 phase and Sn phase. This can be confirmed by the standard cards of Cu, Cu3Sn1 and Sn. (JCPDS PDF#04-0836, JCPDS PDF#01-074-6752 and JCPDS PDF / 04-0673). Figure 3 The structure of the Sn site of the Cu3Sn1 alloy detected by HAAD-STEM is consistent with that of the Sn atom as the termination site, which proves the successful synthesis of the Sn-Cu3Sn1 / Cu catalyst.

[0057] Take 25 mg of Sn-Cu3Sn1 / Cu catalyst and add it to 2500 μL of anhydrous ethanol solvent to make 10 mg ml -1 The ink-like slurry was then added with 150 μL of 5% nafion solution, and the slurry was ultrasonically treated at 60 kHz for 0.5 h. The carbon paper was cut into 25 cm 2 Then wash with ethanol and deionized water and dry. Apply the prepared slurry evenly on the carbon paper with a loading of 1 mg / cm 2The slurry was completely dried by irradiating with a 100W infrared lamp for 50 minutes to obtain a carbon paper-supported Sn-Cu3Sn1 / Cu electrode.

[0058] The prepared carbon paper-loaded Sn-Cu3Sn1 / Cu electrode was placed at the cathode of the flow electrolytic cell as the working electrode, and nickel foam was selected as the counter electrode. -1 The two electrodes were separated by a KOH electrolyte solution. The flow rate was 50 ml min -1 Ethylene-rich feed gas (20% ethylene, 0.5% acetylene, and the rest is argon) containing 0.5% acetylene is introduced into the acetylene gas chamber of the electrocatalytic acetylene hydrogenation reaction system from the gas inlet. The electrochemical workstation is connected to set the working electrode potential to -0.2V, -0.4V, and -0.6V respectively, and the acetylene gas diffuses to the working electrode for electrocatalytic acetylene hydrogenation reaction, so that acetylene is selectively hydrogenated into ethylene. The acetylene hydrogenation gas product discharged from the gas outlet of the acetylene gas chamber is analyzed by gas chromatography.

[0059] At the reaction potential of -0.2 V, the conversion rate of the Sn-Cu3Sn1 / Cu catalyst was 93.5%, the selectivity was 90.4%, and the Faraday efficiency was 89.2%. At the reaction potential of -0.4 V, the conversion rate of the Sn-Cu3Sn1 / Cu catalyst was 100.0%, the selectivity was 92.9%, and the Faraday efficiency was 86.2%. At the reaction potential of -0.6 V, the conversion rate of the Sn-Cu3Sn1 / Cu catalyst was 100.0%, the selectivity was 95.3%, and the Faraday efficiency was 79.1%. At -0.4 V (V vs. RHE) and 50 ml min -1 The data of the conversion rate of the EASR reactants and the FE (%) of the products using the catalyst at a flow rate of Figure 1 .

[0060] Comparative Example 1: Synthesis of Sn / Cu catalyst and its application in electrocatalytic acetylene hydrogenation reaction

[0061] Prepare solution A by dissolving 1.07 g of anhydrous cupric chloride and 0.38 g of stannous chloride in 10 ml of deionized water. Prepare 10 ml of 5 mol L -1 10 ml of sodium borohydride aqueous solution B was quickly added to 10 ml of solution A at 0°C and allowed to stand for 2 hours. The black solid in the solution was collected and then washed with water and ethanol several times. The prepared black solid was dried in a vacuum oven at 40°C for 12 hours. The obtained catalyst was named Sn / Cu, and its XRD pattern is shown in Figure 2 . Figure 2 It is shown that as the molar ratio of metallic Sn increases, the peak representing metallic Sn in the Sn / Cu catalyst increases.

[0062] Take 25 mg of Sn / Cu catalyst and add it to 2500 μL of anhydrous ethanol solvent to make 10 mg ml -1 The ink-like slurry was then added with 150 μL of 5% nafion solution, and the slurry was ultrasonically treated at 60 kHz for 0.5 h. The carbon paper was cut into 25 cm 2 Then wash with ethanol and deionized water and dry. Apply the prepared slurry evenly on the carbon paper with a loading of 1 mg / cm 2 The slurry was completely dried by irradiating with a 100 W infrared lamp for 50 minutes to obtain a carbon paper-supported Sn / Cu electrode.

[0063] The prepared carbon paper-loaded Sn / Cu electrode was placed at the cathode of the flow electrolytic cell as the working electrode, and nickel foam was selected as the counter electrode. -1 The two electrodes were separated by a KOH electrolyte solution. The flow rate was 50 ml min -1 Ethylene-rich feed gas (20% ethylene, 0.5% acetylene, and the rest is argon) containing 0.5% acetylene is introduced into the acetylene gas chamber of the electrocatalytic acetylene hydrogenation reaction system from the gas inlet. The electrochemical workstation is connected to set the working electrode potential to -0.2V, -0.4V, and -0.6V respectively, and the acetylene gas diffuses to the working electrode for electrocatalytic acetylene hydrogenation reaction, so that acetylene is selectively hydrogenated into ethylene. The acetylene hydrogenation gas product discharged from the gas outlet of the acetylene gas chamber is analyzed by gas chromatography.

[0064] When the reaction potential is -0.2V, the conversion rate of the catalyst Sn / Cu is 79.7%, the selectivity is 80.9%, and the Faraday efficiency is 62.5%. When the reaction potential is -0.4V, the conversion rate of the catalyst Sn / Cu is 90.1%, the selectivity is 88.7%, and the Faraday efficiency is 87.3%. When the reaction potential is -0.6V, the conversion rate of the catalyst Sn / Cu is 99.4%, the selectivity is 89.2%, and the Faraday efficiency is 65.6%. At -0.4V (Vvs.RHE) and 50ml min -1 The data of the conversion rate of the EASR reactants and the FE (%) of the products using the catalyst at a flow rate of Figure 1 .

[0065] Comparative Example 2: Synthesis of Cu6Sn4 catalyst and its application in electrocatalytic acetylene hydrogenation reaction

[0066] Dissolve 202 mg of anhydrous copper chloride, 189 mg of stannous chloride and 774 mg of sodium citrate in 20 ml of water to prepare solution A. Stir solution A on a magnetic stirrer for 10 min at room temperature. Prepare a concentration of 0.2 mol L -140 ml of sodium borohydride aqueous solution B was quickly added to 20 ml of solution A and heated at 80 ° C for 5 hours. The black solid in the solution was collected, and then the prepared black solid was washed with water and ethanol several times. It was dried in a vacuum oven at 100 ° C for 12 hours. The obtained catalyst was named Cu6Sn4, and its XRD pattern is shown in Figure 2 .

[0067] Take 25 mg of Cu6Sn4 catalyst and add it to 2500 μL of anhydrous ethanol solvent to make 10 mg L -1 The ink-like slurry was then added with 150 μL of 5% nafion solution, and the slurry was ultrasonically treated at 60 kHz for 0.5 h. The carbon paper was cut into 25 cm 2 Then wash with ethanol and deionized water and dry. Apply the prepared slurry evenly on the carbon paper with a loading of 1 mg / cm 2 The slurry was completely dried by irradiating with a 100W infrared lamp for 50 minutes to obtain a carbon paper-supported Cu6Sn4 electrode.

[0068] The prepared carbon paper-loaded Cu6Sn4 electrode was placed at the cathode of the flow electrolytic cell as the working electrode, and nickel foam was selected as the counter electrode. -1 The two electrodes were separated by a KOH electrolyte solution. The flow rate was 50 ml min -1 Ethylene-rich feed gas (20% ethylene, 0.5% acetylene, and the rest is argon) containing 0.5% acetylene is introduced into the acetylene gas chamber of the electrocatalytic acetylene hydrogenation reaction system from the gas inlet. The electrochemical workstation is connected to set the working electrode potential to -0.2V, -0.4V, and -0.6V respectively, and the acetylene gas diffuses to the working electrode for electrocatalytic acetylene hydrogenation reaction, so that acetylene is selectively hydrogenated into ethylene. The acetylene hydrogenation gas product discharged from the gas outlet of the acetylene gas chamber is analyzed by gas chromatography.

[0069] When the reaction potential is -0.2V, the conversion rate of the catalyst Cu6Sn4 is 20.1%, the selectivity is 71.3%, and the Faraday efficiency is 60.4%. When the reaction potential is -0.4V, the conversion rate of the catalyst Cu6Sn4 is 38.5%, the selectivity is 81.3%, and the Faraday efficiency is 75.5%. When the reaction potential is -0.6V, the conversion rate of the catalyst Cu6Sn4 is 44.6%, the selectivity is 87.1%, and the Faraday efficiency is 50.9%. At -0.4V (Vvs.RHE) and 50ml min -1 The data of the conversion rate of the EASR reactants and the FE (%) of the products using the catalyst at a flow rate of Figure 1 .

[0070] Comparative Example 3: Synthesis of Cu6Sn5 catalyst and its application in electrocatalytic acetylene hydrogenation reaction

[0071] Dissolve 161 mg of anhydrous copper chloride, 189 mg of stannous chloride and 774 mg of sodium citrate in 20 ml of water to prepare solution A. Stir solution A on a magnetic stirrer for 10 min at room temperature. Prepare a concentration of 0.2 mol L -1 40 ml of sodium borohydride aqueous solution B was quickly added to 20 ml of solution A and heated at 80 °C for 5 hours. The black solid in the solution was collected and then washed with water and ethanol several times. Dry in a vacuum oven at 100 °C for 12 hours. The obtained catalyst was named Cu6Sn5, and its XRD pattern is shown in Figure 2 .

[0072] Take 25 mg of Cu6Sn5 catalyst and add it to 2500 μL of anhydrous ethanol solvent to make 10 mg ml -1 The ink-like slurry was then added with 150 μL of 5% nafion solution, and the slurry was ultrasonically treated at 60 kHz for 0.5 h. The carbon paper was cut into 25 cm 2 Then wash with ethanol and deionized water and dry. Apply the prepared slurry evenly on the carbon paper with a loading of 1 mg / cm 2 The slurry was completely dried by irradiating with a 100W infrared lamp for 50 minutes to obtain a carbon paper-supported Cu6Sn5 electrode.

[0073] The prepared carbon paper-loaded Cu6Sn5 electrode was placed at the cathode of the flow electrolytic cell as the working electrode, and nickel foam was selected as the counter electrode. -1 The two electrodes were separated by a KOH electrolyte solution. The flow rate was 50 ml min -1 Ethylene-rich feed gas (20% ethylene, 0.5% acetylene, and argon for the rest) containing 0.5% acetylene is introduced into the acetylene gas chamber of the electrocatalytic acetylene hydrogenation reaction system from the gas inlet. The electrochemical workstation is connected, and the working electrode potential is set to -0.2V, -0.4V, and -0.6V respectively. The acetylene gas diffuses to the working electrode for electrocatalytic acetylene hydrogenation reaction, so that acetylene is selectively hydrogenated into ethylene. The acetylene hydrogenation gas product discharged from the gas outlet of the acetylene gas chamber is analyzed by gas chromatography.

[0074] When the reaction potential is -0.2V, the conversion rate of the catalyst Cu6Sn5 is 25.4%, the selectivity is 75.4%, and the Faraday efficiency is 63.5%. When the reaction potential is -0.4V, the conversion rate of the catalyst Cu6Sn5 is 41.2%, the selectivity is 87.3%, and the Faraday efficiency is 81.5%. When the reaction potential is -0.6V, the conversion rate of the catalyst Cu6Sn5 is 50.1%, the selectivity is 89.8%, and the Faraday efficiency is 55.8%. At -0.4V (Vvs.RHE) and 50ml min-1 The data of the conversion rate of the EASR reactants and the FE (%) of the products using the catalyst at a flow rate of Figure 1 .

[0075] By comparing the catalysts Sn-Cu3Sn1 / Cu, Sn / Cu, Cu6Sn4 and Cu6Sn5 in Example 1 and Comparative Examples 1-3, the 25cm 2 EASR acetylene conversion, product selectivity and FE (%) in the gas chamber. As the surface Sn content of Sn-Cu3Sn1 / Cu increases, Sn / Cu catalyst is formed, and Sn will coat Cu nanoparticles to form a core-shell structure. As a result, the Sn / Cu catalyst fails to completely convert acetylene in the ethylene-rich stream. As the thickness of Sn in the outer layer increases, the byproduct C4 increases, and the ethylene selectivity decreases. Product formation is directly related to the potential. When the potential is -0.2V, the conversion rate of Sn-Cu3Sn1 / Cu catalyst is only 93.5%, and the reaction cannot meet the requirements for complete conversion of acetylene. The optimal reaction conditions of Sn-Cu3Sn1 / Cu catalyst are -0.4V, ethylene FE (%) ≥86.2%, C2H4 selectivity ≥92.9%, and complete conversion of acetylene is achieved.

[0076] Comparative Example 4: Synthesis of Cu catalyst and its application in electrocatalytic acetylene hydrogenation reaction

[0077] Prepare solution A by dissolving 1g of anhydrous copper chloride in 10ml of deionized water. Prepare 10ml of a 5mol L -1 10 ml of sodium borohydride aqueous solution B was quickly added to 10 ml of solution A at 0 °C and allowed to stand for 2 hours. The black solid in the solution was collected and then washed with water and ethanol several times. The prepared black solid was dried in a vacuum oven at 40 °C for 12 hours. The obtained catalyst was named Cu, and its XRD pattern is shown in Figure 2 .Depend on Figure 2 The main diffraction peak positions of the Cu catalyst XRD are shown to be 43.3, 50.4, and 74.1, which are consistent with the positions of the copper standard card, indicating the successful synthesis of the copper catalyst. The Cu catalyst XRD spectrum contains a small amount of Cu2O diffraction peaks, which are inevitably generated by the contact of copper with air during the preparation and testing process.

[0078] Take 25 mg of Cu catalyst and add it to 2500 μL of anhydrous ethanol solvent to make 10 mg ml -1 The ink-like slurry was then added with 150 μL of 5% nafion solution, and the slurry was ultrasonically treated at 60 kHz for 0.5 h. The carbon paper was cut into 25 cm 2Then wash with ethanol and deionized water and dry. Apply the prepared slurry evenly on the carbon paper with a loading of 1 mg / cm 2 The slurry was completely dried by irradiating with a 100 W infrared lamp for 50 minutes to obtain a carbon paper-supported Cu electrode.

[0079] The prepared carbon paper-loaded Cu electrode was placed at the cathode of the flow electrolytic cell as the working electrode, and nickel foam was selected as the counter electrode. -1 The KOH electrolyte solution separates the two electrodes. The flow rate is 50 ml min -1 Ethylene-rich feed gas (20% ethylene, 0.5% acetylene, and the rest is argon) containing 0.5% acetylene is introduced into the acetylene gas chamber of the electrocatalytic acetylene hydrogenation reaction system from the gas inlet. The electrochemical workstation is connected to set the working electrode potential to -0.2V, -0.4V, and -0.6V respectively, and the acetylene gas diffuses to the working electrode for electrocatalytic acetylene hydrogenation reaction, so that acetylene is selectively hydrogenated into ethylene. The acetylene hydrogenation gas product discharged from the gas outlet of the acetylene gas chamber is analyzed by gas chromatography.

[0080] When the reaction potential is -0.2V, the conversion rate of the catalyst Cu is 93.8%, the selectivity is 75.1%, and the Faraday efficiency is 59.1%. When the reaction potential is -0.4V, the conversion rate of the catalyst Cu is 100.0%, the selectivity is 82.1%, and the Faraday efficiency is 47.8%. When the reaction potential is -0.6V, the conversion rate of the catalyst Cu is 100.0%, the selectivity is 84.7%, and the Faraday efficiency is 30.9%. At -0.4V (V vs.RHE) and 50ml min -1 The data of the conversion rate of the EASR reactants and the FE (%) of the products using the catalyst at a flow rate of Figure 1 .

[0081] By comparing Example 1 with Comparative Example 4, the catalyst Sn-Cu3Sn1 / Cu and the catalyst Cu at -0.2V, -0.4V, -0.6V potentials at 25cm 2 The selectivity, FE (%) and acetylene conversion rate of EASR products in the gas chamber. At -0.4V, Cu nanoparticles can achieve complete conversion of acetylene impurities, but the excellent HER performance of Cu nanoparticles reduces the FE (%) of ethylene products to 47.8%, which limits the application of copper catalysts in EASR. Sn metal can effectively inhibit the HER activity of copper nanoparticles. The C2H4 selectivity of Sn-Cu3Sn1 / Cu catalyst is as high as 92.9%. Weak adsorption is formed between Sn termination sites and C2H2, which makes it difficult for carbon-carbon coupling reactions to occur between adjacent C2H2 activated molecules. The FE (%) of Sn-Cu3Sn1 / Cu catalyst reaches a maximum of 86.2%.

[0082] Comparative Example 5: Performance evaluation of Sn-Cu3Sn1 / Cu catalyst at different gas chamber areas

[0083] Cut the carbon removal paper into 1cm 2 The flow rate of the ethylene-rich feed gas (20% ethylene, 0.5% acetylene, and the rest argon) containing 0.5% acetylene was set to 2 ml min -1 In addition, the synthesis of Sn-Cu3Sn1 / Cu catalyst, the preparation and evaluation of carbon paper-supported Sn-Cu3Sn1 / Cu electrode are the same as those in Example 1.

[0084] When the reaction potential is -0.2V, the conversion rate of Sn-Cu3Sn1 / Cu catalyst is 90.5%, the selectivity is 78.4%, and the Faraday efficiency is 83.5%. When the reaction potential is -0.4V, the conversion rate of Sn-Cu3Sn1 / Cu catalyst is 100.0%, the selectivity is 90.9%, and the Faraday efficiency is 80.2%. When the reaction potential is -0.6V, the conversion rate of Sn-Cu3Sn1 / Cu catalyst is 100.0%, the selectivity is 90.9%, and the Faraday efficiency is 80.2%. 1 / The conversion rate of the Cu catalyst was 100.0%, the selectivity was 92.3%, and the Faradaic efficiency was 75.1%.

[0085] By comparing Example 1 with Comparative Example 5, the area of ​​the air chamber is increased from 1 cm 2 Expand to 25cm 2 , Sn-Cu3Sn1 / Cu catalyst achieves a higher removal rate of acetylene impurities. At a potential of -0.4V, the raw gas is at 1cm 2 The gas chamber was heated at 2 ml min -1 The flow rate and at 25cm 2 The air chamber was heated at 50 ml min -1 The gas flow rate can be completely converted into C2H4 with an ethylene selectivity of more than 90%. The expanded reactor can increase the gas flow rate from 2 ml min -1 Increase to 50ml min -1 , achieving complete removal of C2H2 impurities and meeting production requirements. The results of Example 1 and Comparative Example 5 show that Sn-Cu3Sn1 / Cu catalyst has good application prospects for electrochemical removal of ethylene impurities.

[0086] Comparative Example 6: Performance evaluation of Sn-Cu3Sn1 / Cu catalyst under thermal catalytic acetylene hydrogenation conditions

[0087] The Sn-Cu3Sn1 / Cu catalyst was prepared in the same manner as in Example 1. The performance of the Sn-Cu3Sn1 / Cu catalyst in the thermal catalytic selective hydrogenation of acetylene was evaluated in a fixed bed reactor at atmospheric pressure. The flow rate of the ethylene-rich feed gas (20% ethylene, 0.5% acetylene, 10% hydrogen and other argon) was controlled to 50 ml min -1 The reaction temperature was set at 200°C. The acetylene hydrogenation gas products were analyzed using gas chromatography. The conversion rate of the Sn-Cu3Sn1 / Cu catalyst was 55.6% and the selectivity was 40.5%.

[0088] The performance of Sn-Cu3Sn1 / Cu catalyst under the conditions of thermal catalytic acetylene hydrogenation and electrocatalytic acetylene hydrogenation is compared by Example 1 and Comparative Example 6. It can be found that under the conditions of electrocatalysis, Sn-Cu3Sn1 / Cu catalyst has high conversion rate and selectivity, and does not need to consume hydrogen. This makes it possible for electrocatalytic acetylene hydrogenation technology to replace thermal catalytic acetylene hydrogenation technology.

Claims

1. A Sn-Cu3Sn1 / Cu catalyst, characterized in that: The microstructure of the Sn-Cu3Sn1 / Cu catalyst is that a Cu3Sn1 alloy layer is reconstructed on the surface of copper nanoparticles, and Sn atoms are grown on the Sn sites of the Cu3Sn1 alloy as termination sites.

2. A method for preparing the Sn-Cu3Sn1 / Cu catalyst as claimed in claim 1, characterized in that: The preparation method is carried out according to the following steps: Step 1: dissolving copper salt and tin salt in water and stirring to prepare solution A, wherein the molar ratio of Sn / Cu is 0.01-0.2, preferably 0.04-0.06; Step 2: Prepare a solution with a concentration of 0.1-10 mol L -1 of sodium borohydride aqueous solution B; Step 3: Rapidly add sodium borohydride aqueous solution B into solution A at -10°C to 25°C and let stand for 2-6 hours; Step 4: Collect the solid in the solution, wash, and dry to obtain the Sn-Cu3Sn1 / Cu catalyst.

3. The preparation method according to claim 2, characterized in that: The copper salt described in step 1 is selected from at least one of copper chloride, copper nitrate, copper sulfate, copper phosphate, copper pyrophosphate, basic copper carbonate, and copper acetate; the tin salt is selected from at least one of stannous chloride, tin tetrachloride, tin nitrate, and stannous sulfate.

4. A copper-tin catalyst electrode, characterized in that: The copper-tin catalyst electrode is obtained by uniformly mixing a slurry containing the Sn-Cu3Sn1 / Cu catalyst according to claim 1 and a nafion solution with a mass fraction of 5%-25%, uniformly coating the mixed slurry on an electrode material, and then drying.

5. The copper-tin catalyst electrode according to claim 4, characterized in that: The concentration of the slurry containing Sn-Cu3Sn1 / Cu catalyst is 0.5-10 mg ml -1 The ratio of the volume of the slurry containing the Sn-Cu3Sn1 / Cu catalyst to the volume of the nafion solution is 2500:30-200.

6. The copper-tin catalyst electrode according to claim 5, characterized in that: The concentration of the slurry containing the Sn-Cu3Sn1 / Cu catalyst was 10 mg ml -1 The mass fraction of the nafion solution is 5%, and the ratio of the volume of the slurry containing the Sn-Cu3Sn1 / Cu catalyst to the volume of the nafion solution is 2500:

150.

7. The copper-tin catalyst-loaded electrode according to any one of claims 4 to 6, characterized in that: The electrode material is at least one of carbon paper, carbon cloth, foamed nickel and foamed copper.

8. The copper-tin catalyst electrode according to claim 7, characterized in that: The electrode material is carbon paper, and the loading amount of the mixed slurry on the carbon paper is 0.1-2 mg / cm 2 , preferably 0.8 to 1.2 mg / cm 2 .

9. A method for preparing a copper-tin catalyst electrode as claimed in any one of claims 4 to 8, characterized in that: The preparation method is carried out according to the following steps: Step A: Take Sn-Cu3Sn1 / Cu catalyst and add it to the solvent to make 0.5-10mg ml -1 The ink-like slurry is then added with a 5%-25% by mass nafion solution, and the mixed slurry is subjected to ultrasonic treatment to be fully dispersed; Step B: washing and drying the cut electrode materials; Step C: evenly apply the mixed slurry obtained in step A to the electrode material obtained in step B, and irradiate with an infrared lamp until the slurry is completely dry to obtain a copper-tin catalyst-loaded electrode.

10. Use of the supported copper-tin catalyst electrode as claimed in any one of claims 4 to 8 in the electrocatalytic selective hydrogenation reaction of acetylene.

Citation Information

Patent Citations

  • Nanoparticle of copper-tin nuclear shell structure and preparation method for nanoparticle

    CN102554219A

  • Preparation method for silicon carbide coated copper-tin alloy nanoparticle composite material

    CN105895951A

  • Composite copper particles, and method for producing same

    US20150144849A1